2022
DOI: 10.3389/fnut.2022.971879
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association of serum carotenoid levels with prevalence of hypertension in the general adult population

Abstract: Carotenoid levels are inversely associated with blood pressure (BP). This study focused on the effects of individual and combined serum carotenoids on BP and hypertension, which have not been established to date. Data from National Health and Nutrition Examination Survey (NHANES) 2001–2006 were analyzed in this cross-sectional study. Multivariate logistic, linear, and weighted quantile sum (WQS) regression analyses were applied to explore the associations of six serum carotenoids (α-carotene, β-cryptoxanthin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“… 5 Consistent with our observation, serum β-cryptoxanthin has been negatively correlated with SBP in a nationally representative sample of US adults. 33 In the DASH-Sodium trial, urine 3,5-dihydroxybenzoic acid was higher in individuals consuming the DASH versus control diet, and urine levels of theobromine and 3-methylxanthine were lower in individuals consuming the DASH versus control diet. Urine 3,5-dihydroxybenzoic acid has been proposed as a biomarker of whole grain intake.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Consistent with our observation, serum β-cryptoxanthin has been negatively correlated with SBP in a nationally representative sample of US adults. 33 In the DASH-Sodium trial, urine 3,5-dihydroxybenzoic acid was higher in individuals consuming the DASH versus control diet, and urine levels of theobromine and 3-methylxanthine were lower in individuals consuming the DASH versus control diet. Urine 3,5-dihydroxybenzoic acid has been proposed as a biomarker of whole grain intake.…”
Section: Discussionmentioning
confidence: 99%
“…It may function as an antioxidant to decrease serum CRP levels and individual inflammatory burden ( 56 ). Researchers showed that a mixture of carotenoids was inversely associated with blood pressure, among which, trans-β-carotene had the most substantial contribution ( 57 ). Moreover, trans-β-carotene, as a provitamin A, could decrease children’s body mass index (BMI), truncal fat mass, and total body fat mass, while vitamin A exhibited the opposite effects ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The drinking status was divided into three categories: never (less than 12 drinks in a year), former (more than 12 drinks in a year but no longer drinking), and current (more than 12 drinks in a year but still drinking) 20 . Physical activity status was classified as vigorous, moderate and inactive 21 . Diabetes was defined as being informed by doctor/health professional about the diagnosis of diabetes and/or a glycosylated hemoglobin measurement of ≥6.5% 22…”
Section: Methodsmentioning
confidence: 99%
“… 20 Physical activity status was classified as vigorous, moderate and inactive. 21 Diabetes was defined as being informed by doctor/health professional about the diagnosis of diabetes and/or a glycosylated hemoglobin measurement of ≥6.5%. 22 …”
Section: Methodsmentioning
confidence: 99%